Introduction to Digital Business through E-Business, E-Commerce, Website CMS, SEO, and SEM - Rr. Isni Anisah Puspowati Harori; Adi Suwarno; Yasfi Mahadi; Azka Faris Ghalba; Oka Ramdani; Reviya Agustina; Regan Regan; Alfian Alfian; Ajeng Nabila Budiman; Nazwa Nazwa; Argya Argya (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team, comprising academics and students, conducted activities to examine the implementation of digital technology projects that offer substantial opportunities for youth to engage in online business. Many vocational high school students still lack sufficient understanding and skills in modern digital business concepts, such as E-Business, E-Commerce, CMS-based website management, and digital marketing strategies like SEO and SEM. This initiative aimed to provide education and practical training to students at SMK Marhas Margahayu, helping them understand and apply digital business principles. The strategy included interactive workshops with theoretical presentations, direct demonstrations, practical lessons on creating online stores with WordPress, and simulations of digital marketing tactics. Using a pre-test and post-test methodology, along with observations of student participation, the findings revealed significant improvements in students' understanding of digital business and increased interest in entrepreneurship. This initiative aims to promote digital entrepreneurship among vocational high school students and can be replicated in similar institutions.